COVID-19 and Corporate Cash Holdings in Indonesia - Bambang Sutrisno (Indonesian Financial Review, 2021)
The COVID-19 outbreak highly affected the continuity of public firms. Cash holding decisions are one of the captivating issues in the corporate finance area during the COVID-19 pandemic. This study examines the difference in cash holding levels before and after the COVID-19 pandemic. Public firms included in the LQ45 index are examined. By employing a paired-samples t-test, the results show a significant difference in cash holding level before and after the COVID-19 pandemic exists. This result supports the precautionary motive for saving cash amid the COVID-19. This study implies that the managers should increase the cash holding level during the COVID-19 pandemic.